Adsorption of picloram on clays nontronite, illite and kaolinite: equilibrium and herbicide-clays surface complexes. Issue 4 (3rd April 2019) - Marco-Brown, Jose L.; Gaigneaux, Eric M.; Torres Sánchez, Rosa M.; dos Santos Afonso, María
Abstract: The picloram (PCM) adsorption on nontronite, illite and kaolinite was studied at pH 3, 5 and 7. The adsorption isotherms had well-fitted to Langmuir and Freundlich models equations. The interactions of PCM with the clay mineral surfaces exhibited an anionic profile adsorption, with a decrease in adsorption when the pH increases. The PCM adsorption capacity increases in the following order: kaolinite < illite < nontronite. The X-ray diffraction (XRD) analysis of PCM-clay samples revealed that the picloram molecule does not enter into the clays basal space. The interaction of PCM with clays surface sites through nitrogen of the pyridine ring was confirmed by X-ray photoelectron spectroscopy (XPS). Due to the anionic form of PCM, the adsorption onto the external and edges surface sites of the clay minerals was proposed.